Dietary practices and supplement use among CrossFit® participants. Issue 1 (31st December 2022) - Brisebois, Matthew; Kramer, Samuel; Lindsay, Keston G.; Wu, Chien-Ting; Kamla, James
ABSTRACT: Background: CrossFit® is a popular high-intensity functional training program. CrossFit® participants may practice popular diets or consume dietary and sports supplements to support their health or physical pursuits, but the specific dietary and supplement practices of CrossFit® participants remain unknown. Methods: An electronic questionnaire was developed to collect data on practice of popular diets (i.e. Paleo and The Zone Diet®), dietary and sports supplement use, reasons for practicing a diet or using supplements, sources of information on diets and supplements, and various beliefs associated with nutrition among CrossFit® participants. Results: Of the 2, 576 complete responses (female 51.9%, male 48.1%, age 39.4 ± 11.1 years, body mass index 26.1 ± 3.9 kg/m 2 ), 695 (27%) reported being a CrossFit® trainer or coach and 1, 392 (54%) reported competing, or planning to compete, in CrossFit® or other fitness competitions. The average years of CrossFit® experience were 5.3 ± 3.1 years, and the average frequency of CrossFit® participation was 4.5 ± 1.1 days/week. Most participants (60.1%) reported practicing a particular diet. Macro Counting (18.6%), Intermittent Fasting (7.7%), and Paleo (6.1%) were the most frequently reported diets. The top reasons for practicing a diet were to improve overall health (45.6%), decrease body fat (29.2%), and improve CrossFit® performance (25.2%). The top sources of dietary information were the Internet (47.5%), coach/trainer (28.7%), and nutritionist/dietitian (26.2%). Most participants (67.3%) reported "Urine Color" as the best method to assess hydration. Additionally, most participants (82.2%) consumed at least one supplement, with protein (51.2%), creatine (22.9%), and pre-workout/energy (20.7%) being most popular. The top reasons for consuming supplements were to improve recovery (52.6%), improve overall health (51.4%), and increase muscle mass/strength (41.7%). The top sources of information on supplements were the Internet (53.1%), coach/trainer (27.0%), and peer-reviewed research (23.0%). Conclusions: A large proportion of CrossFit® participants may practice popular diets or consume supplements with the intention of improving health or performance. These findings may support future research on the effects of various dietary patterns and supplements on CrossFit® performance.